Comparative microbiome diversity in root-nodules of three Desmodium species used in push-pull cropping system - Adan, Isack H.; Asudi, George Ochieng; Niassy, Saliou; Jalloh, Abdul A.; Mutua, Johnstone Mutiso; Chidawanyika, Frank; Khamis, Fathiya; Khan, Zeyaur; Subramanian, Sevgan; Dubois, Thomas; Mutyambai, Daniel Munyao (Frontiers in Microbiology, 2024)
Background: Desmodium species used as intercrops in push-pull cropping systems are known to repel insect-pests, suppress Striga species spp. weeds, and shift soil microbiome. However, the mechanisms through which Desmodium species spp. impact the soil microbiome, either through its root exudates, or changes in soil nutrition, or shading microbes from its nodules into the rhizosphere, are less understood. Here, we investigated the diversity of root-nodule microbial communitycommunities of three Desmodium speciesspp.-Desmodium uncinatum (SLD), Desmodium intortum (GLD), and Desmodium incanum (AID) which are currently used in smallholder maize push-pull technology (PPT). Methods: Desmodium species spp. root-nodule samples were collected from selected smallholder farms in western Kenya, and genomic DNA was extracted from the root-nodules. The amplicons underwent paired-end Illumina sequencing to assess bacterial and fungal populations. Results: We found no significant differences in composition and relative abundance of bacterial and fungal speciesspp. wwithin the root-nodules of the three Desmodium speciesspp. While a more pronounced shift was observed for fungal community compositions compared to that of bacteria, there were no significant differences were observed in the general diversity (evenness and richness) of fungal and bacterial populations among the three Desmodium speciesspp. Similarly, beta diversity was not significantly different among the three Desmodium speciespp. The root-nodule microbiome of the three Desmodium speciesspp. was dominated by Bradyrhizobium and Fusarium speciespp. Nevertheless, there were significant differences in the proportion of marker gene sequences responsible for energy and amino acid biosynthesis among the three Desmodium species, with higher sequence proportions observed in Desmodium uncinatumSLD.There is no significant difference in the microbial community of the three Desmodium species spp. used in PPT. However, root-nodule microbiome of Desmodium uncinatumSLD had significantly higher marker gene sequences responsible for energy and amino acid biosynthesis. Therefore, it is likely that the root-nodules of the three Desmodium speciesspp. nodules host similar microbiomemicrobiomes and influence soil health and microbiome equally, consequently impacting plant growth and agroecosystem functioning.